Halloween - Sirett, Dawn; Ward, Elle (London Dorling Kindersley Limited, 2017)
"From bumpy pumpkins to furry black kittens, there are all sorts of textures for baby to explore in this safe, study book that encourages early learning"--Back cover
Picture books
1 2 23
Keywords: Picture book for children